Saffron vegetative growth as affected by transplanting and direct corm planting under field conditions - Hamid-Reza Fallahi (University of Birjand, 2021)
Purpose: One of the main challenges of saffron production under controlled environments (CE) is that when flowering ends, there is no specific plan for corm proliferation. It seems that transplanting can provide economic justification for saffron production in CE, by providing the possibility of replacement corms production. This study aimed to evaluate the possibility and effectiveness of transplanting of those corms that previously flowered in controlled condition. Research method: To compare the vegetative growth of saffron between two planting methods including direct planting (DP) and transplanting (TP) an experiment was conducted. In the TP method, corms that were flowered under CE were transplanted to four plots beside the plots of DP. At the end of the growing season, leaf and replacement corms (RC) criteria were measured in both planting methods. Findings: Leaf length and weight in DP were 19.5 and 85.1 % more than TP, respectively. Mean RC weight (4.01 vs. 2.35 g), the weight of main RC (14.22 vs. 9.56 g), and number of buds with flowering potential (1.87 vs. 1.28 No. per corm), in DP was more than TP. The number of RC (524 vs. 612 corms per m2) was higher in TP, while RC yield (2093 vs. 1432 g m2) was more in DP method. The percentage of large RC (> 9g) in DP and TP was 19.8 and 6.5 %, respectively. Also, 68 and 32 % of RC yields were belonged to large corms, in DP and TP methods, respectively. Limitations: This study was one of the first studies on saffron transplanting, and the methodologies should be improved in future studies to gain more favorable results. Originality/Value: It was concluded that transplanting of those corms which were flowered under CE is possible, and at least one-third of the RC yield was at the desired weight.